Ophthalmic phenotypes associated with biallelic loss‐of‐function PCDH12 variants. Issue 4 (2nd February 2021) - Mattioli, Francesca; Voisin, Norine; Preikšaitienė, Eglė; Kozlovskaja, Irina; Kučinskas, Vaidutis; Reymond, Alexandre
Abstract: Individuals carrying biallelic loss‐of‐function mutations in PCDH12 have been reported with three different conditions: the diencephalic–mesencephalic junction dysplasia syndrome 1 (DMJDS1), a disorder characterized by global developmental delay, microcephaly, dystonia, and a midbrain malformation at the diencephalic–mesencephalic junction; cerebral palsy combined with a neurodevelopmental disorder; and cerebellar ataxia with retinopathy. We report an additional patient carrying a homozygous PCDH12 frameshift, whose anamnesis combines the most recurrent DMJDS1 clinical features, that is, global developmental delay, microcephaly, and ataxia, with exudative vitreoretinopathy. This case and previously published DMJDS1 patients presenting with nonspecific visual impairments and ophthalmic disorders suggest that ophthalmic alterations are an integral part of clinical features associated with PCDH12 loss‐of‐function.